The role of recombinant proteins in the development of serum-free media - Keenan, Joanne (Springer Netherlands, 2006)
Early developments in serum-free media led to a variety of formulations in which components normally provided in serum and required for growth (insulin, transferrin, lipid supplements, trace elements) and poorly defined components (extracts, hydrolysates) were added to defined basal media. These additives were mostly animal-derived. Given recent concerns about TSEs (transmissible spongiform encephalopathies) and other adventitious agents, the drive in media formulations must be towards elimination of animal-origin materials while maintaining cell line productivity. The progress made towards removing animal-derived components and the use of recombinant proteins in serum-free media for mammalian cells is reviewed.